Factors affecting the enforcement of environmental regulation: The case of erosion and sediment control plan - Ng, C. C.; R. A., Rahman; S. W., Ahmad (IOP Publishing Ltd., 2021)
Construction activities significantly increase the amount of sediment loss from sites due to erosion. Hence, governments are implementing environmental regulations, including the Erosion and Sediment Control Plan (ESCP), to reduce the construction industry's impact on the environment. Prior studies suggest that effective enforcement by government bodies is crucial to ensure proper ESCP implementation. Therefore, this study aims to identify the success factors and challenges of enforcing ESCP in practice. To achieve that objective, this study employs a qualitative research technique that compares ESCP guidelines between countries. The significant results include: (a) the challenges are in the aspect of the hierarchy of authorities, lack of information in the guidelines, and enforcement that are lenient; and (b) the success factors include the elements of having detailed information in guidelines, a suitable period is given to all parties, and frequent inspections. These findings can assist researchers and government bodies to develop strategies to enforce ESCP better. The development of better strategies would help improve the success of ESCP implementation. This paper contributes to the body of knowledge in analyzing enforcement strategies in existing guidelines and standards for ESCP.